The Effect of Nursing Interventions on Community Health Deficiency Problems in Adolescents in Sleman, Indonesia - suwarsi, suwarsi; Amanda, Zahra; Inta, Pornpan (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2025)
Adolescents are known as a solid and mutually influential social group, so that behavioral patterns are often uniform. However, this uniformity can be a challenge and also increase the risk of developing a community health deficit. This occurs because of the lack of knowledge of adolescents about sexually transmitted diseases, the impact of smoking, and a lack of understanding of available health services. These conditions underline the need for comprehensive health education and a proactive community nursing approach. This study aims to improve the effectiveness of community-based health education in enriching adolescents' understanding of STDs, the dangers of smoking, access to health services, and other risky behaviors through adolescent posyandu activities. The study design used a quasi-experimental approach with a one-group pre-test and post-test model. A total sample of 96 adolescents in Pokoh, Sleman, Indonesia. Education was provided simultaneously, with standardized instruments that have been validated and following the principles of research ethics. Data analysis was carried out using the Wilcoxon test. The results showed a significant increase in adolescents' understanding of the dangers of smoking and access to health services after the intervention. However, the increase in knowledge of other risky behaviors was not significant. These findings strengthen the important role of community nurses as the spearhead in addressing community health deficits through sustainable educational and preventive strategies.